(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
A field experiment was carried out at the Agricultural Research Station of the College of Agriculture - University of Basrah during the winter season of 2021-2022 to study the effect of adding different levels of triple superphosphate fertilizer compared to Nano-phosphate fertilizer on the vegetative growth characteristics of wheat (Triticum aestivum L.). Triple super phosphate fertilizer at levels 0, 30, 60 and 90 kg Pha-1 when planting, and Nano-phosphate fertilizer at levels 0, 5, 10 and 15 kg Pha-1 was added as a sprinkler on the plant at the stages of branching and elongation, Crop growth rate from 50% heading stage to full maturity, Dry weight, phosphorus concentration in dry matter and phosphorus up take at the end of the season. The results showed no significant differences in the studied traits (Crop growth rate from 50% heading stage to full maturity, Dry weight, phosphorus concentration in dry matter and phosphorus up take) between the two sources of phosphate fertilizer despite the added amount of Nano-fertilizer representing (1/4) of the amount of triple superphosphate fertilizer, and the results also indicated that the increase in phosphorous levels The addition of 0 to 90 kg of triple superphosphate and from 0 to 10 kg of Pha-1 of Nano phosphate fertilizer led to an increase in growth vocabulary, but the addition of Nano fertilizer at the level of 15 kg of Pha-1 led to a decrease in all growth vocabulary. The results indicated the superiority of the cultivar Ibaa-99 in the characteristics (Dry weight, phosphorus concentration in dry matter and phosphorus uptake).